Comparative study of electrolyte thermodynamic models for carbon dioxide solubility in water at high pressure - Suleman, H. (Italian Association of Chemical Engineering - AIDIC, 2015)
The electrolyte thermodynamic models have been extensively studied for carbon dioxide - water system for the prediction of vapour liquid equilibrium at low pressures. However, no guidelines are available for selection of electrolytic models which are applicable at high pressure for prediction of thermodynamic properties. In this study, solubility prediction of limited Debye Huckel (DH), Pitzer Debye Huckel (PDH) and modified Three Characteristic Parameter Correlation (mTCPC) electrolyte models have been tested for a wide range of temperature (273-453 K) and pressure (0.1-7.2 MPa).The comparative study shows that introduction of electrolyte model improves the prediction accuracy when physical solubility of gas is low, either in high temperature or low pressure region. The mTCPC model gives improved prediction than nonelectrolyte model but requires additional parameters and complex calculations. New values for binary interaction parameters of UNIFAC for carbon dioxide - water system are also optimized. Copyright Â© 2015, AIDIC Servizi S.r.l.,.